Pancreatic Squamous Cell Carcinoma - Seyed Hassan Abedi (Case Reports in Gastroenterology, 2017)
Pancreatic squamous cell carcinoma (SCC) is a rare event. Here, we present a 56-year-old man with pancreatic SCC. Imaging methods demonstrated a hypodense mass at the head and trunk of the pancreas. Also, some lymphadenopathy has been seen around the pancreas and para-aorta. The mass created pressure and encasement on the celiac trunk, portal vein, and arteries of the liver and spleen. Endoscopic ultrasound showed a mass lesion of 45–37 mm (mixed echoic) at the trunk of the pancreas. Histological examination of the endoscopic ultrasound-guided fine needle aspiration specimen confirmed the diagnosis of SCC. The disease is highly aggressive, most often locally advanced or metastatic at diagnosis, and poorly responsive to treatment. It also has generally poor survival rates.